Acantomatous ameloblastoma: Case report and review of the literature - Larios-León, Javier (2020)
Introduction. Ameloblastoma is a rare benign tumor, occasionally with aggressive behavior, originating from enamel-producing cells. Located most frequently in the mandible, having its highest incidence between the 4th 5th decade of life, generally asymptomatic, imaging studies being the fundamental diagnostic test. Case report: We present the case of a 43-year-old woman with a progressively growing tumor in the left lower jaw, without functional limitation. The CT of the mandible shows an osteolytic and expansive lesion with defined edges, which breaks the anterior cortex, infiltrating soft tissues; she is subjected to tumor extraction associated with curettage; jointly in the pathology, Acantomatous Ameloblastoma is identified. Conclusion: Acantomatous ameloblastoma has a long recurrence-free survival if its diagnosis is timely and its treatment is multidisciplinary, including surgery and radiotherapy, although its rarity causes difficulty in finding the best available treatment.